Leachate From Expanded Polystyrene Cups Is Toxic to Aquatic Invertebrates (Ceriodaphnia dubia) - Thaysen, Clara; Stevack, Kathleen; Ruffolo, Ralph; Poirier, David; De Frond, Hannah; DeVera, Julieta; Sheng, Grace; Rochman, Chelsea M. (Frontiers in Marine Science, 2018)
Expanded polystyrene (EPS) products and their associated chemicals (e.g., styrenes) are widespread in the marine environment. As a consequence, bans on their use for single-use packaging materials are being proposed in several municipalities. To better understand how science can inform decision-making, we looked at the available scientific literature about contamination and effects and conducted experiments to measure chemical leachate from polystyrene products and toxicity from the leachate. We conducted leaching experiments with common food matrices (water, soup broth, gravy, black coffee and coffee with cream and sugar) at relevant temperatures (70ºC and 95ºC) that are consumed in or with several polystyrene products (coffee cup lids, polystyrene stir sticks, polystyrene spoons, EPS cups, EPS bowls and EPS takeout containers). We analyzed each sample for styrene, ethylbenzene, toluene, benzene, meta- and para- xylene, isopropylbenzene, and isopropyltoluene – chemicals associated with polystyrene products. To determine whether the leachates are toxic, we conducted chronic toxicity tests, measuring survival and reproductive output in Ceriodaphnia dubia. Toxicity tests included nine treatments: seven concentrations of ethylbenzene, EPS cup leachate and a negative control. Overall, we found that temperature has a significant effect on leaching. We only detected leachates in trials conducted at higher temperature – 95ºC. Ethylbenzene was the only target analyte with final concentrations above the method limit of detection, and was present in the greatest concentrations in EPS and with soup broth. Measurable concentrations of ethylbenzene in the leachate ranged from 1.3 to 3.4 µg/L. In toxicity tests, the calculated LC50 for ethylbenzene was 14 mg/L and the calculated LC20 was 210 µg/L. For the treatment exposed to the EPS cup leachate, mortality was 40% - four times greater than the negative control. Finally, there was no significant difference (p = 0.17) between reproductive output for any treatment with ethylbenzene, but there was a significant reduction (p = 0.01) in reproductive output for the treatment exposed to the EPS leachate compared to the negative control. Thus, although the target analyte ethylbenzene was not toxic at concentrations detected in the leachate, significant adverse effects were detected in the whole EPS cup leachate sample.